2007
DOI: 10.1073/pnas.0609863104
|View full text |Cite
|
Sign up to set email alerts
|

Smad-interacting protein-1 (Zfhx1b) acts upstream of Wnt signaling in the mouse hippocampus and controls its formation

Abstract: Smad-interacting protein-1 (Sip1) [Zinc finger homeobox (Zfhx1b)] is a transcription factor implicated in the genesis of Mowat-Wilson syndrome in humans. Sip1 expression in the dorsal telencephalon of mouse embryos was documented from E12.5. We inactivated the gene specifically in cortical precursors. This resulted in the lack of the entire hippocampal formation. Sip1 mutant mice exhibited death of differentiating cells and decreased proliferation in the region of the prospective hippocampus and dentate gyrus.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
109
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 86 publications
(110 citation statements)
references
References 38 publications
1
109
0
Order By: Relevance
“…Moreover, BMP2 and BMP4 induce Dkk1 expression during limb development in mouse and chicken (Grotewold and Ruther, 2002;Mukhopadhyay et al, 2001). In addition, other studies suggest possible cross-talk between SFRPs and BMP signaling (Ellies et al, 2000;Miquelajauregui et al, 2007;Oshima et al, 2005). However, the present study provides the first in vivo evidence that BMP/TGF relies on SMAD4 to regulate Dkk1 and Sfrp1 expression during dentinogenesis.…”
Section: Dkk1 and Sfrp1 Are Downstream Targets Of Smad4supporting
confidence: 44%
“…Moreover, BMP2 and BMP4 induce Dkk1 expression during limb development in mouse and chicken (Grotewold and Ruther, 2002;Mukhopadhyay et al, 2001). In addition, other studies suggest possible cross-talk between SFRPs and BMP signaling (Ellies et al, 2000;Miquelajauregui et al, 2007;Oshima et al, 2005). However, the present study provides the first in vivo evidence that BMP/TGF relies on SMAD4 to regulate Dkk1 and Sfrp1 expression during dentinogenesis.…”
Section: Dkk1 and Sfrp1 Are Downstream Targets Of Smad4supporting
confidence: 44%
“…We have previously shown that deletion of Sip1 in postmitotic neurons has severe effects on cortical development (Miquelajauregui et al, 2007;Seuntjens et al, 2009). We had demonstrated that Sip1 deletion in young neocortical neurons changes the proportion of DL versus UL neurons.…”
Section: Resultsmentioning
confidence: 97%
“…Sip1 transcripts are detected at the onset of neurogenesis in the postmitotic cells of the mouse neocortex, with barely detectable levels in progenitors 18 . By immunohistochemistry, we found high Sip1 protein levels in the cortical plate, but none in progenitors (Fig.…”
Section: Sip1 Levels Are High In Postmitotic Neocortical Cellsmentioning
confidence: 99%